„A Tobie? Ile brakuje do szczęścia?” O socjalizacyjnych możliwościach reklamy - Kałuzińska, Emilia (Forum Lingwistyczne, 2016)
“And You? How Much are You Lacking in Happiness?” The Socialization Abilities of Advertising In this text Emilia Kałuzińska is trying to reconstruct socializing offer of advertising. For this purpose, she analyzes the linguistic picture of the world in the spoken texts ads shown on children’s channel. High vocabulary attendance in the field of buying and selling contributes to extract CONSUMPTION AREA, among which stands out exposing of NEWNESS, as well as LOANS that are in commercials autotelic value. Key words: media socialization, advertisement, child, Polish of consumer